The Role of Teachers in Increasing Students' Motivation to Learn Arabic - Nisa, Dina Qurotun; Permana, Johar; Rahyasih, Yayah (Graduate School of Universitas Negeri Malang, 2024)
The motivation to learn is crucial for achieving optimal educational outcomes. The motivation to learn Arabic is uniquely relevant due to the prevalence of Islamic educational institutions offering it as part of their curriculum. This study aims to identify and analyze the role of teachers in increasing students' motivation to learn Arabic in schools. This research employs a qualitative approach with a systematic literature review (SLR) method. The data used are secondary data sourced from various online databases, including Google Scholar and accredited national and international journals. The data collection technique involves documentation. Data analysis is conducted through five stages: summarizing, synthesizing, comparing, contrasting, and critiquing the literature. The study identifies several key roles of teachers in boosting students' motivation to learn Arabic: educator, mentor, coach, advisor, leader, role model, and community member. Teachers play a crucial role in creating a supportive and motivating learning environment. Effective teachers use personalized instruction, motivational remarks, and technology to engage students. Mentors provide academic and emotional support, while coaches use active learning strategies. Advisors give constructive feedback, and leaders inspire and set positive examples. Role models influence students' attitudes and behaviors, and community members enrich the learning experience by integrating it with students' daily lives. These roles collectively contribute to a more motivated and engaged learning environment. Understanding the multifaceted roles of teachers can help develop more effective strategies to enhance students' motivation to learn Arabic, contributing significantly to educational practice in Indonesia.